Aktualisasi Gaya Hidup Halal Dalam Pola Konsumsi Santri - Rohim, Ade Nur; Priyatno, Prima Dwi (Al-Sharf: Jurnal Ekonomi Islam, 2024)
Pesantren is an Islamic educational institution that has a distinctive educational system in shaping students’ lifestyles. It is necessary to have a process of identifying the pattern of a halal lifestyle, applied in pesantren, so that it can be implemented in a wider community. This study aims to identify the consumption patterns of students with a halal lifestyle approach in Al Jadid Islamic Boarding School, Serang Banten. The method used is a qualitative research method using primary and secondary data. The results showed that the implementation of the students' halal consumption began with the implementation of a pesantren policy that directed students to a halal lifestyle, by providing halal food, goods, and medicines. In addition, the awareness of students regarding halal consumption is built through education and literacy which is carried out through learning processes. This awareness is manifested in the students' understanding of the meaning of consumption in Islam, implementing Islamic consumption behavior, and carrying out Islamic financial planning.